2013
DOI: 10.4172/2161-1076.1000184
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Procalcitonin in the Management of Small Bowel Obstruction: A Preliminary Report

Abstract: The PCT kinetics' study participants were divided into two groups: patients in whom the CM was successful (the CM group, n=47) and those in whom it had failed (the SM group, n=12).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…We reported that when measured with the Kryptor TRACE method, the PCT values ranged from 0.29 ng/mL to 2.03 ng/mL in patients with ischemia. Moreover, we validated these data in a second, distinct cohort of 59 patients treated for small bowel obstruction by showing that PCT values (measured with the same assay) ranged from 0.06 ng/mL to 8.1 ng/mL in individuals with intraoperatively confirmed ischemia [37] . Our group also evaluated the value of PCT for characterizing tissue damage in cases of intestinal ischemic diseases (including ischemic colitis and mesenteric infarction) [38] .…”
Section: Assay Methodsmentioning
confidence: 70%
See 1 more Smart Citation
“…We reported that when measured with the Kryptor TRACE method, the PCT values ranged from 0.29 ng/mL to 2.03 ng/mL in patients with ischemia. Moreover, we validated these data in a second, distinct cohort of 59 patients treated for small bowel obstruction by showing that PCT values (measured with the same assay) ranged from 0.06 ng/mL to 8.1 ng/mL in individuals with intraoperatively confirmed ischemia [37] . Our group also evaluated the value of PCT for characterizing tissue damage in cases of intestinal ischemic diseases (including ischemic colitis and mesenteric infarction) [38] .…”
Section: Assay Methodsmentioning
confidence: 70%
“…Nagata et al [36] Open aortic surgery 93 < 0.5 -> 10 Immunochromatographic test Markogiannakis et al [22] Small and large bowel obstruction 242 4.89-14.35 LUMItest Cosse et al [23] Small bowel obstruction 166 0.29-2.03 Kryptor TRACE Cosse et al [37] Small bowel obstruction 59 0.06-8.1 Kryptor TRACE Cosse et al [38] Ischemic disease (ischemic colitis and mesenteric infarction) 99 0.217-621.2 Kryptor TRACE Table 3 Diagnostic utility of procalcitonin for the diagnosis of intestinal ischemia clinical trial [23] . We reported that when measured with the Kryptor TRACE method, the PCT values ranged from 0.29 ng/mL to 2.03 ng/mL in patients with ischemia.…”
Section: Assay Methodsmentioning
confidence: 99%
“…These mediators induce the release of PCT from intestinal macrophages and hepatocytes through the portal system 14 . A prospective non-randomized study conducted with 59 patients diagnosed with small bowel obstruction showed that the surgical treatment achieved cutoff value by measuring PCT levels every 6 h. The cutoff value was 0.16 ng/mL at first admission and was >0.27 ng/mL at the 18th hour 15 . In another study of 242 cases that predicted surgical treatment, the authors emphasized that PCT levels in the treatment of ileus could play an essential role in clinical decision-making in acute bowel obstruction, and they proceeded to surgery with value >1 ng/mL 16 .…”
Section: Discussionmentioning
confidence: 99%
“…In 2005, Ayten et al reported for the rst time the association between procalcitonin (PCT) increase and I/N in rabbits (12). Subsequently, multiples studies investigated the role of PCT in the management and prognosis of adult patients with adhesive small bowel obstruction (ASBO) showing encouraging results (13)(14)(15)(16)(17)(18). In 2017, we published the rst study in pediatric patients that demonstrated correlation between the increase in PCT and presence of I/N in patients with ASBO (19) and suggested that a PCT greater than 1.0 ng/ml should be indicative of surgical management due to this association.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, this study was exclusive for patients with ASBO including those managed with medical treatment and surgery; we got some false negatives, which we believe were from taking PCT every 24 hours or maybe because we granted that ABSO that didn't require surgery had no I/N. In the current study, we only included patients with IO who required surgical intervention, meaning we were certain of the presence/absence of I/N and we attempted to reduce false negatives by taking the last sample of PCT immediately before surgery knowing the report that recommended taking PCT more frequently (15).…”
Section: Introductionmentioning
confidence: 99%